Impact of physical activity on the prevention of breast cancer in postmenopausal women: A Protocol for systematic review and meta-analysis - Juliana Dantas de Araújo Santos Camargo; Sávio F. Camargo; Amaxsell Thiago Barros de Souza; Ana Karla M. S. de Oliveira Freitas; Maria L. Nobre; Ayane C. A. Sarmento; Antônio C. Q. de Aquino; Ana Beatriz D. Oliveira; Nicoli Serquiz; Ana Katherine Gonçalves (Journal of Education and Health Promotion)
Breast cancer is responsible for the highest rates of incidence and mortality among neoplasms in women. There is a lack of evidence regarding the different domains and intensities of physical activity (PA) in relation to the risk of breast cancer occurrence in menopause. The objective will be to evaluate the impact of different domains and intensities of PA in preventing breast cancer in postmenopausal women. Databases, including MEDLINE/PubMed, Scopus, Web of Science, and Embase, will be used for the search. A search strategy was developed to retrieve observational studies (case–control and cohort) that have evaluated occurrence of breast cancer and practice of PA in postmenopausal women. No date or language restrictions will be applied. Two authors will independently select the studies meeting the inclusion criteria by screening the title, abstract, and full text. Data will be extracted, and the risk of bias will be evaluated using the Newcastle–Ottawa scale (NOS). Review Manager 5.4.1 and software R version 4.3.1 will be used for data synthesis. The Grading of Recommendation Assessment, Development, and Evaluation will be used to assess the strength of the evidence. This systematic review and meta-analysis will summarize the comparative efficacy of types, domains and intensities of PA in reducing the risk of breast cancer in postmenopausal women.